Coxiella burnetii blood cultures from acute and chronic Q-fever patients. - Musso, D (1995)
Q fever, a worldwide zoonosis caused by Coxiella burnetii, may present as either an acute or a chronic disease. We correlated the results of 844 C. burnetii blood cultures with serological, clinical, and therapeutic data. C. burnetii was isolated from 17% of untreated patients with acute Q fever and from 53% of untreated patients with chronic Q fever. C. burnetii was not isolated from patients who were receiving antibiotics active against C. burnetii. For seven culture-positive patients with acute Q fever, serology was negative when C. burnetii was isolated. One patient with acute Q fever had a positive blood culture 25 days after the discontinuation of specific antibiotic therapy, and another had a positive blood culture after the resolution of symptoms. In one case of chronic Q fever, a positive blood culture resulted from noncompliance with treatment. The culture method described in this report is suitable for all laboratories with cell culture facilities. Our findings suggest that blood samples must be collected prior to the initiation of an antibiotic regimen if C. burnetii is to be successfully isolated.